If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 9 = -13 + -7x Reorder the terms: 9 + 4x = -13 + -7x Solving 9 + 4x = -13 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 9 + 4x + 7x = -13 + -7x + 7x Combine like terms: 4x + 7x = 11x 9 + 11x = -13 + -7x + 7x Combine like terms: -7x + 7x = 0 9 + 11x = -13 + 0 9 + 11x = -13 Add '-9' to each side of the equation. 9 + -9 + 11x = -13 + -9 Combine like terms: 9 + -9 = 0 0 + 11x = -13 + -9 11x = -13 + -9 Combine like terms: -13 + -9 = -22 11x = -22 Divide each side by '11'. x = -2 Simplifying x = -2
| y-(-7)=6(x-(-4)) | | 7-10x=23-24x | | y-(-7)=-6(x-(-7)) | | 10x+18=5x+128 | | 2x-3y+4=0 | | 12x-5y=0 | | 10x+8=5x+128 | | 89-2x=3x+24 | | 160-7x=20x+19 | | 5x+6=-84-10x | | y=3(5)+23 | | 4x+31=12x-49 | | 7y-12=9 | | 4r+6=22 | | e-15=16 | | 6t=42 | | w-9=5 | | 11x+12=6x+102 | | h+7=15 | | 105-2x=25x+18 | | 12-9x=67-44x | | (n+4)x*4=48 | | 94-2x=43x-19 | | 126-5x=5x+6 | | 6a-6=42 | | 125-3x=5x+21 | | 237-3x=42x+22 | | 3n=12 | | 3x+2=18-5x | | x+8=3+2x | | 5x+13=-39-8x | | 114-2x=9x+18 |